REFLECTIONS ON ARCHITECTURAL RESEARCH - Alba-Dorado, María Isabel; González Bandera, María Isabel (IATED Academy, 2020)
This communication attempts to defend a research method that has the objective of opening the way within this field, establishing a permanent dialog with teaching and using that which underlies everything architectural as a work strategy, so that the implicit creative and transforming essence remains in architectural research. Thus, as the architectural project is conceived as a research process linked to a creative activity, research in the field of architecture can be understood as a creative process that, as such, is linked to a reflective and speculative activity It is a question, therefore, of committing to a research that finds its independence as much in action as in reflection as opposed to the procedures and methodologies of other disciplines. Consequently, a research method is demanded from the field of architecture, which, as opposed to a mode of knowledge based on logical thought, recognizes that a knowledge based on a poetic thought also exists. In this sense, research in the field of architecture should be understood not as a mere accumulation of data but as a creative activity that, far from linking to a static knowledge, establishes a dialectic process between thought and action. This leads us to transfer, in undertaking all research, that sensation of extreme freedom comparable only with the moment when we face the architectural project with a blank sheet and entails a sensation of uncertainty and insecurity only surmountable through the risk involved in throwing thoughts and ideas onto the desk that, although precise, are supported on most occasions by non-verifiable realities or hardly demonstrable in their totality. Therefore, a research method is demanded that departs from the study of architecture in its singularity and specificity, but which refrains from establishing a systematic and deductive process as the only mode of knowledge, as well as of attempting to find the reliability of ideas and thoughts in a rational and objective model.
Keywords: Arquitectura - Estudio y enseñanza; research; architecture; trends; experiences; teaching